2017
DOI: 10.4236/ojra.2017.71008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Etiology of Viral Arthropathies in West African Patients

Abstract: Aim: To determine the frequency and etiology of viral arthritis in West African patients at the National Hospital University Hubert Koutoukou Maga of Cotonou. Patients and Methods: It was a cross-sectional descriptive study carried out from January 2010 to July 2014 on patients received in rheumatology, hepato-gastroenterology, pediatric and internal medicine units. The selected patients had viral arthropathy. The diagnosis of viral arthritis was based on the presence of arthralgia or arthritis in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…At the time of diagnosis, the most common clinical picture is a combination of cutaneous and articular manifestations. Systemic lupus erythematosus, although rare, was found in first place in our study, and in second place in most African studies; it appears to be more common in the North African region [8] [11]. In Burkina Faso, systemic scleroderma was the leading cause in 33% of cases, compared with 21% in our series.…”
Section: Rheumatoid Arthritis Is the Most Frequently Described Type O...supporting
confidence: 41%
See 2 more Smart Citations
“…At the time of diagnosis, the most common clinical picture is a combination of cutaneous and articular manifestations. Systemic lupus erythematosus, although rare, was found in first place in our study, and in second place in most African studies; it appears to be more common in the North African region [8] [11]. In Burkina Faso, systemic scleroderma was the leading cause in 33% of cases, compared with 21% in our series.…”
Section: Rheumatoid Arthritis Is the Most Frequently Described Type O...supporting
confidence: 41%
“…One hypothesis to explain the rarity of autoimmune diseases in sub-Saharan Africa is the abnormally high concentration of nitric oxide in patients who have had asymptomatic malaria; this increase in nitric oxide is thought to have a protective effect by reducing the proliferation of auto-reactive cells, making these diseases rare in this part of the world. Gougerot Sjögren's disease has been poorly described in some African studies (0.8% in Benin and 0.3% in Central Africa), but 32 cases were reported in a study carried out in Dakar [8] [11]. We have reported seven cases of isolated dermato-polymyositis in which no neoplasia was diagnosed.…”
Section: Rheumatoid Arthritis Is the Most Frequently Described Type O...mentioning
confidence: 72%
See 1 more Smart Citation
“…In Benin, the available data on lupus comes mainly from two studies based on relatively old data dating back 10 years. These studies showed that lupus is rare, with 33 cases in 14 years, a clinical polymorphism and a case-fatality rate in excess of 12% [5] [6]. These high mortality rates, despite the therapeutic advances of recent decades, highlight the need for improved and optimized disease management in hospitals.…”
Section: Introductionmentioning
confidence: 99%